LINGKUNGAN ARTIFISIAL DALAM PEMBELAJARAN BAHASA ARAB - Nur Habibah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
This research was aimed at proving whether artificial language environment affect Arabic language skills and analyzing how the artificial language environment impact the skills. The method used in this research was categorized into a field research which combined both qualitative and quantitative method, or well-known as mixed method. The primary source in this research was taken from the 1st and 2nd grade of senior high madrasah Pondok Pesantren Madinatunnajah Jombang Ciputat, South Tangerang academic year 2015/2016. Moreover, the secondary source was obtained from some literatures in the form of academic journals and books related to this study. The research found that environment-based language learning was more effective and influential on listening, speaking, reading, and writing skills of Arabic language. It was concluded that language skills are not only determined by LAD (Language Acquisition Device), a gifted device to acquire language, but also determined by the environment the learner lived.DOI : 10.15408/a.v3i2.4038